Adoption of Blockchain Technology in Indonesian MSME Supply Chain Management (SCM). - Wiji Safitri; Miftakul Huda (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
MSMEs are the economic driving sector, but at this time there are many fraud in this sector. The main problem of MSMEs is Supply Chain Management. Blockchain technology is believed to be a solution. The purpose of this study is to determine the adoption of blockchain in the supply chain management for Indonesian MSMEs. This research was conducted on 193 Indonesian MSMEs. Data was collected by distributing online questionnaires. The method used is Structural Equation Modeling (SEM). Data is processed using Smart PLS. The results of this study are competitive pressure significantly affect behavior in intention, complexity has no significant effect on behavioral intention, complexity has a significant effect on the cost, complexity has a significant effect on upper management support, cost has no significant effect on behavioral intention, market dynamics has no significant effect on behavioral intention, Regulatory Support does not significantly effect on behavioral intention, relative advantage has a significant effect on behavioral intention, relative advantage has a significant effect on the cost, relative advantage significantly influences upper management support, and upper management support significantly affect behavior intention. From the results of this study, the results obtained that MSMEs believe the blockchain can facilitate supply chain but there must be a clear legal support and cost to adopt the blockchain.